2010
DOI: 10.1111/j.1462-5822.2009.01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling parasite dissemination: host cell subversion and immune evasion byToxoplasma gondii

Abstract: SummaryProtozoan parasites belong to the most widespread and devastating human pathogens. Their ability to manipulate host responses and establish infection in their hosts continues to puzzle researchers. Recent developments of experimental model systems are contributing to the discovery of new aspects of the biology of parasite dissemination. Here, we review current knowledge on strategies utilized by the apicomplexan parasite Toxoplasma gondii to disseminate and establish infection in its host. Recent findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 55 publications
(104 reference statements)
1
82
1
5
Order By: Relevance
“…Several studies have demonstrated that immune cells infected with T. gondii become hypermotile (27)(28)(29)(30)(31)(32)(33)(34)41), an effect that has been proposed to facilitate the dissemination of the intracellular parasite in the infected host. In the present study, we have demonstrated that the hypermotility of T. gondii-infected human monocytes is linked to a dysregulation in integrin-dependent cell adhesion through defects in FAK-regulated focal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that immune cells infected with T. gondii become hypermotile (27)(28)(29)(30)(31)(32)(33)(34)41), an effect that has been proposed to facilitate the dissemination of the intracellular parasite in the infected host. In the present study, we have demonstrated that the hypermotility of T. gondii-infected human monocytes is linked to a dysregulation in integrin-dependent cell adhesion through defects in FAK-regulated focal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…T. gondii disseminates throughout the bloodstream within either infected monocytes or dendritic cells, as well as via free tachyzoites (65,66), indicating that organs like the brain, eye, and placenta would be invaded when the par- asite traverses endothelial layers. Although the mechanisms of invasion are not well established, one of them appears to entail the migration of the parasite into the brain and presumably the eye within infected leukocytes (65)(66)(67). Extracellular tachyzoites could potentially enter organs, including the placenta if the parasite infects endothelial cells (transcellular traversal) or if the parasite migrates between endothelial cells (paracellular traversal) (67).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting immune response and/or drugs can control tachyzoite replication, but the parasite survives by converting into slow growing bradyzoites that encyst. Cysts sporadically burst, and the released parasites convert to tachyzoites whose unabated growth, as can occur in immune suppressed hosts, results in cell and tissue damage (4). Currently, no Toxoplasma vaccine exists; anti-toxoplasmosis drugs have severe side effects, and resistance to these drugs is occurring.…”
mentioning
confidence: 99%